Prevention of Stress Related Mucosal Disease with Intermittent - Farshid Rahimi-Bashar; Alireza Rastgouyhaghi; Saadat Torabian; MohammadReza Hajiesmaeili; Alireza Sedaghat; Shahram Seifi; Mahdis Solhjoo (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: This study aimed to compare intermittent intravenous (IV) pantoprazole and ranitidine for control of gastric acid secretion and the possible prevention of Upper Gastrointestinal Bleeding (UGIB) in critical care patients. Methods: This was a randomized, double blind clinical trial study of IV pantoprazole (40 mg every12 hour) or intermittent IV ranitidine (50 mg bolus every 8 hour) in patients at risk for UGIB. The primary endpoint was gastric pH. UGIB was measured as secondary endpoint. Results: ninety two Critical care patients were enrolled. Gastric pH was well controlled by two study drugs. Gastric pH increased in pantoprazole group than in the ranitidine group (4.40±0.39 versus 3.32±0.28; P=0.000). Upper GI bleeding was higher in ranitidine group than pantoprazole group (4/46 versus 2/46; P=0.404). Conclusion: This  study  indicates  that  intermittent  IV pantoprazole  compared  with  bolus  IV ranitidine, more effectively controls gastric pH and may prevent UGIB in high risk critical care patients without the development of tolerance.